2004
DOI: 10.1074/jbc.m405635200
|View full text |Cite
|
Sign up to set email alerts
|

Dual Action of Antimonial Drugs on Thiol Redox Metabolism in the Human Pathogen Leishmania donovani

Abstract: Despite extensive use of antimonial compounds in the treatment of leishmaniasis, their mode of action remains uncertain. Here we show that trivalent antimony (Sb III ) interferes with trypanothione metabolism in drug-sensitive Leishmania parasites by two inherently distinct mechanisms. First, Sb III decreases thiol buffering capacity by inducing rapid efflux of intracellular trypanothione and glutathione in approximately equimolar amounts. Second, Sb III inhibits trypanothione reductase in intact cells resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
247
0
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(260 citation statements)
references
References 54 publications
4
247
0
9
Order By: Relevance
“…Although the mode of SbIII's action against Leishmania is poorly understood, mechanisms of resistance have been extensively described and involve the modulation of SbIII detoxifying pathways (36,37), altered uptake (19,38), increased efflux (39), and intracellular sequestration mediated by the ABC-thiol transporter multidrug resistance protein A (MRPA) (37,(40)(41)(42). The Cos-Seq screen for SbIII revealed 11 enriched cosmids ( Fig.…”
Section: High-throughput Screening Of the Five Major Antileishmanial mentioning
confidence: 99%
“…Although the mode of SbIII's action against Leishmania is poorly understood, mechanisms of resistance have been extensively described and involve the modulation of SbIII detoxifying pathways (36,37), altered uptake (19,38), increased efflux (39), and intracellular sequestration mediated by the ABC-thiol transporter multidrug resistance protein A (MRPA) (37,(40)(41)(42). The Cos-Seq screen for SbIII revealed 11 enriched cosmids ( Fig.…”
Section: High-throughput Screening Of the Five Major Antileishmanial mentioning
confidence: 99%
“…La cepa fue seleccionada hasta 37 mg/ml de antimonio pentavalente, debido a que se buscó tener un espectro de resistencia bastante amplio entre la cepa sensible y la resistente (CE 50 de 4 mg/ ml versus 37 mg/ml) y con mayor probabilidad de detectar proteínas asociadas al fenotipo resistente. En esta cepa resistente, se encontró expresión exagerada de las proteínas Hsp60 mitocondrial, Hsp70 mitocondrial y citosólica, proteína de isomerasa de disulfuro y dos proteínas hipotéticas nombradas como Sp(2) y Sp (25), las cuales aparentemente podrían estar participando en una respuesta inicial del parásito para evadir la acción leishmanicida del antimonio pentavalente de manera indirecta, contribuyendo al mecanismo primario de desintoxicación mediado por las moléculas de tripanotión-glutatión al eliminar las formas disulfuro de estos compuestos (19). Además, estas proteínas podrían contribuir a evitar la pérdida del potencial de membrana mitocondrial, controlar el potencial de oxidorreducción de la célula y evitar los procesos de apoptosis de fragmentación del ADN inducido por los antimoniales pentavalentes.…”
Section: Discussionunclassified
“…El antimonio pentavalente es suministrado como un promedicamento que requiere ser activado a antimonio trivalente; no se tiene claro si su activación se produce por una vía enzimática o de manera espontánea (19). Se han reportado varios blancos celulares para el antimonio pentavalente y el antimonio trivalente , incluyendo el tripanotión, que es el principal agente reductor de tioles en el parásito (20)(21)(22).…”
unclassified
“…The route of entry of SbV into Leishmania cells is still unknown but SbIII has been reported to be transported in Leishmania through aquaglyceroporin (AQP1) [11,12]. Recent evidence has suggested that part of the mode of ©NJB, Biotechnology Society of Nepal 2 Nepjol.info/index.php/njb action of SbV could be in depleting the cells of its reduced thiols [13]. Trypanothione (TSH), a major reduced thiol of Leishmania is a N 1 , N8 bisglutathione spermidine conjugate.…”
Section: Introductionmentioning
confidence: 99%